Archaeometric Studies on Hellenistic Period New Type Phaselis Amphorae - Orhan, Uğurcan; Eroğlu, Murat; Kadıoğlu, Yusuf Kağan (Journal of Archaeology, Ege University, 2025)
The primary theme of this study pertains to the archaeometric analyses and outcomes derived from a series of amphorae unearthed during the research conducted at the Phaselis Central Tower (PMK) Ceramic Dumpster (Bothros) and Amphora Production Area. In this study, a range of 8 samples were subjected to mineralogical-petrographic analysis using polarising microscopy and chemical analysis via X-Ray Fluorescence (PED-XRF). In order to determine the texture, mineral and matrix composition of the ceramics for microscopic identification, petrographic analyses were used. A total of eight distinct samples of amphora were thus subjected to a comparative analysis, encompassing both the analysis data of the earlier Hellenistic Temple samples (APK) and the raw clay extracted from the lagoon (raw clay). This approach was undertaken with the objective of ascertaining the consistency of the samples. In this study, the focus was placed on evaluations within the context of archaeology, geology and geography, with the aim of expanding the scope beyond the limitations of archaeometric analysis data alone. Indeed, the objective of this study is to avoid the potential limitations of a hypothetical approach by providing a foundation of concrete evidence derived from diverse disciplinary perspectives. In this regard, the results of the archaeometric studies conducted on the amphorae retrieved during the archaeological excavations were found to be in accordance with the geology of Phaselis. Furthermore, the new Phaselis amphorae type exhibits a high degree of similarity with the raw clay from the Lagoon and other local groups. Consequently, this study, which integrates archaeological, archaeometric, geological and geographical data, is also significant in terms of its interdisciplinary, mutually supportive evidence. In conclusion, it is anticipated that the findings of these studies will make significant contributions to both the amphora studies in the city and the field of ceramology.